HUBUNGAN BIMBINGAN ORANG TUA DENGAN HASIL BELAJAR (KOGNITIF) SISWA PADA MATA PELAJARAN PAI DI SMPN 2 TIGO NAGARI KABUPATEN PASAMAN - Aisyah Syafitri; Muhiddinur Kamal; Salmi Wati; Charles Charles (KOLONI, 2022)
This research is motivated by the phenomenon of the author's observations about students who indicated that they had received parental guidance but had low learning outcomes. This study uses a quantitative correlation approach. Collecting data in this study the authors obtained through questionnaires and documentation. This study used 294 students as the population and as many as 44 students as samples taken from 15 people at each level of class VIII, IX and 14 people in class VII. The data analysis technique that the author uses is a prerequisite analysis test in the form of a data normality test and a linearity test. Then the final data analysis the author uses is correlation analysis. Based on the results of the study, it can be understood that the significance level between the parental guidance variable (X) and student learning outcomes (Y) students is tcount = 7.52 with rcount = 0.610, then the hypothesis is accepted which states that there is a significant positive relationship between parental guidance and student learning outcomes (cognitive) on PAI subjects, it means H0 is rejected. This is due to = 0.610 which is in the coefficient interval 0.60-0.799 so that the level of correlation between the two variables is included in the strong category. Keyword: Parental Guidance, Learning Outcomes